2019
DOI: 10.1108/yc-03-2019-0973
|View full text |Cite
|
Sign up to set email alerts
|

Children’s pester power, packaging and unhealthy food preference

Abstract: Purpose This study aims to understand the extent to which packaging influences Brazilian parents' purchasing willingness based on children's food preferences for unhealthy food products. Design/methodology/approach Parents, with children up to 12 years old, answered questions about the positive influence of the packaging on the children, the preferences of the children in their willingness to buy and the propensity to give in to the desires of the children. Data analysis was performed with the statistical so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Interestingly, they do not perceive them as overweight or obese even though their children's weight, body mass index might and overall physical appearance may suggest this is the case. Instead, external influences such as external diagnostic (e.g., doctor) or their child's limited physical activity will alarm parents/tutors, while they find it emotionally challenging to refuse food to a hungry child (Eckstein et al 2006;He and Evans 2007;Jain et al 2001) or difficult to resist the "pester power" (Christino et al 2019;Elliott 2011;Marshall, O'Donohoe and Kline 2007;McDermott et al 2006). Such emotional and perceptual filtering by tutors complicates the containment of the overweight/obesity pandemic.…”
Section: Example Of Marketing Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, they do not perceive them as overweight or obese even though their children's weight, body mass index might and overall physical appearance may suggest this is the case. Instead, external influences such as external diagnostic (e.g., doctor) or their child's limited physical activity will alarm parents/tutors, while they find it emotionally challenging to refuse food to a hungry child (Eckstein et al 2006;He and Evans 2007;Jain et al 2001) or difficult to resist the "pester power" (Christino et al 2019;Elliott 2011;Marshall, O'Donohoe and Kline 2007;McDermott et al 2006). Such emotional and perceptual filtering by tutors complicates the containment of the overweight/obesity pandemic.…”
Section: Example Of Marketing Strategiesmentioning
confidence: 99%
“…The Prescriber Child (B3). Knowing the ambivalent role of tutors, marketers tend to use children to drag tutors towards giving into junk food while downplaying its adverse effects, what past research unanimously called the "pester effect" or "nag factor" (Christino et al 2019;Dougherty 2014;Elliott 2011;Lawlor and Prothero 2011;Marshall, O'Donohoe and Kline 2007;McDermott et al 2006). Children may send their tutors a formal request to purchase junk food directly or take a product by themselves without asking for permission.…”
Section: Example Of Marketing Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have published using one-wave cross-sectional survey with focusing on food preference in children or adolescents, studies on food preference of adults are less reported [5][6][7][8]. As children are usually taken care of by their parents, their dietary intake often depends on the family context and their food knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, this study asks whether consumers still buy when the packaging designs do not use flagrant colors and attractive typography and whether color differences in food packagings lead to different individual perceptions. Color plays a big role to attract the children (Zhang, 2013).Children are memorized the colors, shapes, size and illustrations on the packaging (Christino, Cardozo, Silva, & Mazzini, 2019). Color can be used to attract customers on an emotional level (Krishna, Cian, & Aydinoglu, 2016).As reported by Liputan6, Betina Piqueras-Fiszmanfrom the Polytechnic University of Valencia, Spain, and Charles Spence from the University of Oxford, the UK, invited 57 volunteers to taste hot chocolate served in plastic glasses in various colors, such as red, orange, white, and beige with the white color inside the glasses.…”
Section: Introductionmentioning
confidence: 99%